Antiepileptics in Electroconvulsive Therapy: A Mechanism-Based Review of Recent Literature. Issue 2 (3rd June 2022) - Cinderella, Margaret A.; Nichols, Nona A.; Munjal, Sahil; Yan, Jason; Kimball, James N.; Gligorovic, Predrag
Abstract: Although prior conventional wisdom strongly recommended complete discontinuation of medications increasing the seizure threshold before electroconvulsive therapy (ECT), more recent literature suggests that anticonvulsants should be considered a relative rather than an absolute contraindication to proceeding with therapy. Most literature regarding the use of use antiepileptic drugs in ECT focuses on antiepileptic mood stabilizers with which most psychiatrists are familiar. However, there is considerably less information available about the use of newer antiepileptics in conjunction with ECT, which may be prescribed to a patient with epilepsy or off-label for psychiatric reasons. In this article, we provide a mechanism-based review of recent available literature concerning the use of antiepileptics during ECT and discuss which medications have the most robust evidence supporting their continued use in select patients. Finally, we highlight important considerations for psychiatrists when deciding how to proceed with patients on antiepileptics who require ECT.